Games and simulations in online learning research and development frameworks - Gibson, David 1950-.; Aldrich, Clark 1967-.; Prensky, Marc.; Gale Group (Hershey, Penn. Information Science Pub., 2007)
"This book examines the potential of games and simulations in online learning, and how the future could look as developers learn to use the emerging capabilities of the Semantic Web. It explores how the Semantic Web will impact education and how games and simulations can evolve to become robust teaching resources"--Provided by publisher.
Situating games and simulations in education -- Social analyses of games and simulations -- What teachers should know and be able to do -- Using real space in digital games and simulations -- Embedding assessment in games and simulations.
Electronic reproduction.
Keywords: Education -- Simulation methods; Computer games; Computer-assisted instruction; Electronic books